FITOKIMIA 5 JENIS POHON DI KHDTK UNIVERSITAS LAMBUNG MANGKURAT MANDIANGIN KALIMANTAN SELATAN - Agung Wibisono; Sunardi Sunardi; Rosidah R Radam (Jurnal Sylva Scienteae, 2020)
Aims of the study is to identify phytochemical components (alkaloid, flavonoid, saponin, quinone, triterpenoid, and tannin) of 5 species growth in University of Lambung Mangkurat (ULM) Kawasan Hutan Dengan Tujuan Khusus (KHDTK = Education and Training Forest) area. These species are Madang Pirawas, Margatahan, Alaban Timbasu, Rawa Rawa Pipit, and Pulantan. Chemical analysis conducted in Wood Chemistry Laboratory, Faculty of Forestry ULM. The result shows that alkaloid component is found in Madang Pirawas, Margatahan, Alaban Timbasu, Rawa Rawa Pipit, and Pulantan’s leaves. Alaban Timbasu has more alkaloid than the others. Flavonoid component is found in Madang Pirawas, Margatahan, Rawa Rawa Pipit, and Pulantan’s leaves.Rawa Rawa Pipit has more flavonoid than the others. Saponin component is found in Madang Pirawas, Margatahan, Alaban Timbasu, Rawa Rawa Pipit, and Pulantan’s leaves. Pulantan has more saponin than the others. Quinone component is found in Madang Pirawas, Margatahan, Alaban Timbasu, Rawa Rawa Pipit, and Pulantan’s leaves. Madang Pirawas has more quinone than the others. Steroid component is found in Margatahan, Alaban Timbasu, and Rawa Rawa Pipit’s leaves. Alaban Timbasu has more steroid than the others.Triterpenoids component is found in Margatahan, Alaban Timbasu, and Rawa Rawa Pipit’s leaves. Alaban Timbasu has more triterpenoid than the others.Tannin component is found in Madang Pirawas, Margatahan, Rawa Rawa Pipit and Pulantan’s leaves. Rawa Rawa Pipit has more tannin than the others.